Lifestyle among Sports Students: Correlations of Physical Activity, Smoking, Coffee, Screen Time, and Sleep Quality - Hani Astari; Kunjung Ashadi (Masters Program in Public Health, 2025)
Background: A healthy lifestyle is an important factor in achieving a high quality of life.. However, research exploring the impact of smoking habits on physical activity levels among students remains limited. This study aims to determine the correlation between smoking habits and physical activity among sports students. Subjects and Methods: This quantitative research study employed a simple random sampling technique to select 105 students from the Sports Coaching Education program. The students completed self-administered questionnaires to assess their daily smoking habits and weekly physical activity levels. In this study, smoking habits are the dependent variable, while physical activity is the independent variable. The data were analyzed using the Spearman Correlation Test to determine the strength and direction of the relationship between the two variables. Results: The results indicated that 26% of the student population were active smokers, and 27% had insufficient levels of physical activity. Although no statistically significant correlation (p= 0.627) was found between smoking habits and physical activity among the students, a negative correlation trend (r= -0.048) was observed. This suggests that higher smoking levels may be associated with decreased physical activity levels. Conclusion: These results demonstrate that increased smoking may reduce physical activity participation. Therefore, promoting healthy lifestyles among students is crucial for enhancing their life quality.